PELATIHAN PEMBUATAN SABUN CAIR UNTUK PERABOT RUMAH TANGGA DI PATOSAN, MAGELANG, JAWA TENGAH - Ani (LPPM IST AKPRIND Yogyakarta, 2021)
Dishwashing soap is a viscous liquid that can serve to clean kitchen utensils. Thedemand for this product is expected to increase along with the daily lifestyle of people. Inthe market, there are many dishwashing liquid soap products. However, some peoples didnot realize that it is easy to make this product by ourselves at a lower cost. On March 1,2020, at Patosan Village, Sedayu, Muntilan, Magelang, Central Java, we conducted atraining program to make liquid soap. This activity aims to improve liquid soap knowledgeand make it an alternative to getting liquid soap for dishwashers whis is cheaper than theliquid soap products on the market. In the future, this activity is expected to be an inspirationfor entrepreneurship among the villagers. This training was carried out with a presentationfrom a trainer and the practice of making dish soap. The activity was then continued with aquestion and answer session with the trainees. Explanation of training materials could runsmoothly. The PKK’s women group were enthusiastic about this training. The result of thistraining is liquid dishwashing soap and its economic analysis.